(untitled) (Research, Society and Development, 2024)
Objectives: To describe the profile of respiratory support and the process of weaning from invasive mechanical ventilation in patients admitted to the adult intensive care unit (ICU) of a university hospital and to comparatively evaluate the clinical outcomes of these patients in relation to the type of respiratory support used. Methodology: This was a descriptive longitudinal observational study of patients admitted to the hospital’s Adult ICU between 10/16/2023 and 12/15/2023 and aged 18 years or older. Results: A homogeneous patient profile was found, with a predominance of overweight in both groups and an estimated higher risk of mortality in the intubated group. There was a predominance of patients admitted without ventilatory support, with low-flow oxygen therapy (FiO2 <40%). The group of patients admitted intubated to the ICU were predominantly ventilated in controlled mode, with rapid extubation and lower mortality. On the other hand, the group of patients who underwent orotracheal intubation (OTI) in the ICU were mostly ventilated in spontaneous mode, with high mortality before extubation and higher mortality than the other group. Conclusion: There is a predominance of ICU admissions of patients without ventilatory support. Post-operative patients generally require invasive mechanical ventilation and when they undergo OTI they remain mechanically ventilated for less time than those who are intubated in the ICU in emergency situations. The highest mortality rate was observed in those who underwent OTI. The process of ventilator weaning up to extubation can vary when there is no internal hospital protocol.